2018
DOI: 10.1158/2326-6066.cir-17-0415
|View full text |Cite
|
Sign up to set email alerts
|

Maelstrom Directs Myeloid-Derived Suppressor Cells to Promote Esophageal Squamous Cell Carcinoma Progression via Activation of the Akt1/RelA/IL8 Signaling Pathway

Abstract: () is a novel cancer/testis-associated gene, which is not only expressed in the male testicular germ cells among human normal tissues, but is also aberrantly expressed in various cancer tissues. In our study, was characterized as a tumor-promoting gene and was significantly associated with esophageal squamous cell carcinoma (ESCC) recurrence and unfavorable prognosis. Kaplan-Meier analysis showed that patients with high expression had a shorter survival time. Functional experiments showed that promoted tumor c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…IL8 plays an important role in angiogenesis, survival, tumor stemness, invasion, metastasis, and immune cell infiltration in breast, lung, prostate, and pancreatic cancer 46 . In ESCC, IL8 directly binds to CXCR1/2 to promote invasion and migration 47,48 . IL8 also recruits myeloid-derived suppressor cells by chemotaxis to promote tumor cell growth 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL8 plays an important role in angiogenesis, survival, tumor stemness, invasion, metastasis, and immune cell infiltration in breast, lung, prostate, and pancreatic cancer 46 . In ESCC, IL8 directly binds to CXCR1/2 to promote invasion and migration 47,48 . IL8 also recruits myeloid-derived suppressor cells by chemotaxis to promote tumor cell growth 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In ESCC, IL8 directly binds to CXCR1/2 to promote invasion and migration 47,48 . IL8 also recruits myeloid-derived suppressor cells by chemotaxis to promote tumor cell growth 48 . IL8 is associated with progression, metastasis, inflammation, and poor prognosis in ESCC patients 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Of its reported actions, IL-8 has been linked to the recruitment and activation of MDSCs, neutrophils, and other myeloid cell populations to the tumor microenvironment, and the serum concentration of IL-8 is predictive of responses to immunotherapies in melanoma and non-small-cell lung cancer (17, 18). Additionally, it has recently been shown that IL-8 recruits PMN-MDSCs to esophageal squamous cell carcinoma tumors, where the MDSCs promote disease progression and decrease overall survival via TGFβ-mediated Smad2/3 signaling (19). Furthermore, in models of pancreatic cancer, recruitment of MDSCs via IL-8 contributes to the establishment of the metastatic niche, and inhibition of IL-8 reduces the frequency of hepatic metastasis (20).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the NF-κB pathway is often considered an important link between the in ammatory microenvironment and tumor development 41 . The cytokines downstream of NF-κB in ESCC have been reported to be IL-8 and IL1 2,10,24 . IL1 promotes tumor invasion, tumor-mediated immunosuppression, and tumor stem cell self-renewal28.…”
Section: Discussionmentioning
confidence: 99%